Essayistic Thinking – Humanistic Mythology - Mazrimienė, Ilma (Literatūra, 2016)
In this paper is introduced theory on essay and essayism of Mikhail Epstein. M. Epstein (Михаил Наумович Эпштейн) – literary critic, philosopher and cultural anthropologist and essayist, cultural theory and Russian literature professor at Emory University in the USA and Durham University in Great Britain. Epstein discusses the essay genre characteristics and together essayistic thinking spread of other genres in general and various cultural forms. In order to demonstrate the practical application of the theory of literary research, is analyzed together Leonardo Gutausko novel Vilko dantų karoliai (A Wolf Teeth Necklace) the first book (1990). It is proposed to call this novel essays or essays. The thesis describes features characteristic to the essay genre, offers a comparison of essay to novel, and essay to myth, revealing attribution of role of a new mythology to art. This leads to certain structural principles governing essay: reach for integrity, certainty (reality) in a piece of work, organisation and thematic regulation of paradigmatic discourse. It all shapes a certain understanding of essayistic thinking, and simultaneously turns into respective tangible aspects, in turn used to carry out an analysis. The thesis then follows on to concept of essayism, in terms of cultural phenomenon; this has allowed going beyond the form of essay genre.The starting point is individualisation of a myth. According to Epstein, essayistic thinking has inherited from ancient mythology a principle of combing into unity; however, syncretism has been replaced with synthetism, using differentiated forms of culture for mediation purposes.The thesis discovers principle of essayistic thinking in the prose. Image-based thinking of works by Gutauskas is considered a sign of individualisation of a myth. Art then becomes an intermediary, allowing for an overall view of spiritual world of an individual.It is shown that graphically separated fragments can be read as an individual essay or combined into a whole – as essayistic novel. On the whole it combines Tadas’ personality. Personal experience – this text material.Theoretical approach selected has led to discovery of essayistic thinking as dominant in the work of Gutauskas. This in turn allows for a specific, rather than an abstract, definition of the art by the author in question, true to scientific interests, and labelling it an essayistic art, which, through personality of the author, i. e. cultural entity (an individual), combines different levels of culture and reaches an entirety with a cultural dissection. And it is the art that takes on a role of new mythology.
Keywords: ...